PENGARUH PERMAINAN ULAR TANGGA DIGITAL TERHADAP KEMAMPUAN NUMERASI ANAK USIA 5-6 TAHUN DITAMAN KANAK-KANAK - Rahma Fadilla; Yaswinda; Setiyo Utoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the importance of early numeracy skills for children aged 5-6 years and the need for interactive, technology-based learning media to stimulate cognitive development in mathematics. The objective of this study was to determine the effect of the digital snakes and ladders game on early numeracy skills at TK Negeri 1 Padang. This study used a quantitative approach with a quasi-experimental design. The research sample consisted of two classes, class B3 as the experimental group and class B2 as the control group, each consisting of 15 children. The experimental group received learning activities using the digital snakes and ladders game via a Smart Board, while the control group used a conventional paper snakes and ladders game. Data were collected through a pre-test and post-test checklist observation instrument and analyzed using normality, homogeneity, and hypothesis testing (Independent Samples T-Test) with SPSS Version 27. The results showed that the average pre-test score of the experimental class was 20.60 and increased to 32.33 in the post-test, while the control class increased from an average of 19.80 to 24.13. Based on the hypothesis test, the Sig. (2-tailed) value was ¡0.001 (p ¡ 0.05), indicating that Ha is accepted and Ho is rejected. It can be concluded that there is a significant effect of using the digital snakes and ladders game on the early numeracy skills of children at TK Negeri 1Padang.